The Influence of Profitability, Liquidity, Leverage and Company Size on Dividend Policy - Sapruwan, Muhammad; Ulfa, Maria; Dyah, Siti Halimah Tusa; Dasman, Sunita (Lentera Ilmu Nusantara, 2023)
Several food and beverage companies experienced a decrease and increase in the nominal dividend distribution to investors. This research aims to analyze the influence of profitability, liquidity, leverage and company size on dividend policy in food and beverage sub-sector companies listed on the IDX for the 2018-2021 period. The method used is panel data regression analysis obtained from Ordinary Least Square estimation using a fixed effect modelling approach. Profitability is measured by Return on assets (ROA), liquidity by Current Ratio (CR), leverage by Debt-to-Equity Ratio (DER), company size by the natural logarithm of total assets, and dividend policy by Dividend Pay-out Ratio (DPR). The research results show that profitability has a positive effect on dividend policy. Meanwhile, liquidity, leverage and company size have no effect on dividend policy.